The role of Statistics in the Conditions of the “New Normal” - ANNA V. Tikhonova (Учёт. Анализ. Аудит, 2019)
The article is devoted to the pressing problem of the strengthening of the role of statistics and official statistical accounting under the conditions of the “new normal”. World experience of functioning of the national statistical services testifies to the colossal importance of statistics in the activity of any state. The resulting statistical data are the basis for making administrative decisions. In this regard in this particular study we aimed at determining the place and role of national statistics in economic conditions and realias, that Russia was reduced to. For this reason, the first part of the research is devoted to the study of the category of the “new normal” and the role of statistics in the conditions given. Then the research considers practical examples that determine the need to strengthen the role of statistics in Russia on an example of the scope of tax and legal regulations. At the end of the article the author presents the main conclusions of the research, including the author’s proposals aimed at improving the national statistical system and enhancing the reliability of the data. Methodical research tools include a comparative analysis methods and analytical methods of cognition. The scientific article is prepared within the framework of the all-university complex theme of the Financial University under the government of the Russian Federation.